Sequencing justice: a longitudinal study of justice goals of domestic violence victims - Holder, Robyn L. (The British journal of criminology, 2018)
What women as victims of domestic violence want from criminal justice has long interested researchers and advocates. This article foregrounds the ways in which ‘justice’ matters to victims and how a desire for justice may change over time. We find that victims have multiple justice goals, which are ordered and unfold through the criminal justice process. The goals are directed towards three domains of victim, offender and community; and are influenced by both personal and public interests. Accountability is a threshold goal from which others—punishment, deterrence, rehabilitation or another—may be contemplated. From the perspective of victims, achieving justice is sequencing these goals through hybrid processes with differing degrees of victim participation.